DESIGNING A MODEL OF MANAGERS’ COMPETENCE BASED ON THE RELATIONSHIP BETWEEN COMPETENCY DOMAINS AND COMPETENCY DIMENSIONS ACCORDING TO THEIR DECISION MAKING STYLE IN SOCIAL SECURITY ORGANIZATION - Mohammadnia, Afsaneh; Tavakoli, Alireza; Salajegheh, Sanjaher (Revista Inclusiones, 2019)
The purpose of this study was to design a model of competency managers based on the relationship between competency domains and competency competencies based on their decision making style in the social security organization. The statistical population of the present study consists of two groups. The first group consists of experts familiar with merit theory, whose number is unspecified and dispersed throughout the country. Their selection is selectively, and in this section the compilation and The design of the model has been used for them And the second group consists of senior managers, middle managers and social security organizations (2764 people), who work in the 31 departments of social security and treatment in 31 provinces, which according to the Cochran formula, 337 of them Sample title was selected. The methodology was descriptivesurvey research and in collecting data, the questionnaires of competency domain, managerial competency dimensions and decision styles were used. The validity of the questionnaire was 0/91.5, 0/94.9, 0/93.8, with a reliability of 0/86 , 0/91, 0/94.6, are used. Data were analyzed using descriptive and inferential methods such as Pearson correlation coefficient test, single-variable ttest, Kolmogorov-Smirnov test, exploratory and confirmatory factor analysis and SPSS version 21, MINITAB version 17 and LISREL 8/8 editions. Considering the average for competency domain domains, their competency dimensions and decision making style in the social security organization, these variables are more than satisfactory. The results indicate that there is a significant relationship between the competency domain with the dimensions of managers’ competence in the social security organization.